Laparoscopic approach to ventral incisional hernia: absorbable or non-absorbable tacks? —a meta-analysis - Barone, Mirko; Raimondi, Paolo; Caldaralo, Francesco; Cichella, Annadomenica; Tannous, Mouner; Ciampaglia, Franco; Cipollone, Giuseppe; Cotellese, Roberto; Mucilli, Felice; Innocenti, Paolo; Di Bartolomeo, Nicola (Laparoscopic Surgery, 2018)
Background: To compare feasibility andeffectiveness of absorbable and non-absorbable mesh fixation techniques inlaparoscopic ventral incisional hernia repair. Methods: A PubMed Embase, Google Scholarsystematic review was carried out. Primary and secondary endpoints wereconsidered. Odds ratio (OR) for each item was pooled and no bias according toQUADAS-2 tool and funnel plot asymmetry test were found. Results: Five randomized controlled trials,including 1,091 patients, were enrolled. There was no difference between thetwo techniques in terms of postoperative morbidity (OR: 1.03, P=0.910), seromas(OR: 0.77, P=0.520), adhesion formations (OR: 0.49, P=0.560) and chronic pain(OR: 0.81, P=0.260). Risk of recurrence was significantly higher in theabsorbable group (OR: 1.67, P